2011
DOI: 10.1124/jpet.111.184119
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylmethcathinone (Mephedrone): Neuropharmacological Effects of a Designer Stimulant of Abuse

Abstract: The designer stimulant 4-methylmethcathinone (mephedrone) is among the most popular of the derivatives of the naturally occurring psychostimulant cathinone. Mephedrone has been readily available for legal purchase both online and in some stores and has been promoted by aggressive Web-based marketing. Its abuse in many countries, including the United States, is a serious public health concern. Owing largely to its recent emergence, there are no formal pharmacodynamic or pharmacokinetic studies of mephedrone. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
296
7
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(335 citation statements)
references
References 34 publications
22
296
7
5
Order By: Relevance
“…3,4-Methylenedioxypyrovalerone and monoamine transporters MH Baumann et al there are conflicting reports in the literature regarding the precise interactions of designer cathinones with monoamine transporters (Baumann et al, 2012;Cozzi et al, 1999;Hadlock et al, 2011;Martinez-Clemente et al, 2011;Nagai et al, 2007;Sogawa et al, 2011). Our results from in vitro experiments in synaptosomes confirm that uptake inhibition assays can identify drugs which interact with transporter proteins.…”
Section: Discussionsupporting
confidence: 78%
“…3,4-Methylenedioxypyrovalerone and monoamine transporters MH Baumann et al there are conflicting reports in the literature regarding the precise interactions of designer cathinones with monoamine transporters (Baumann et al, 2012;Cozzi et al, 1999;Hadlock et al, 2011;Martinez-Clemente et al, 2011;Nagai et al, 2007;Sogawa et al, 2011). Our results from in vitro experiments in synaptosomes confirm that uptake inhibition assays can identify drugs which interact with transporter proteins.…”
Section: Discussionsupporting
confidence: 78%
“…Plasma samples were extracted as described above. The extraction 7 of brain samples was carried out as described by Hadlock et al (2011) and brain mephedrone levels and protein binding assays were quantified as described in the pharmacokinetic experiments.…”
Section: Protein Binding and Brain Levelsmentioning
confidence: 99%
“…In this study mephedrone was administered orally and urine was collected over a 24-hour period. Hadlock et al (2011) assessed mephedrone concentrations in rat brain and plasma 1 h after a binge treatment and more recently (Khreit et al 2012) investigated the in vitro metabolism of mephedrone in rat isolated hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated subcutaneous (s.c.) administration of either drug to single-housed rats (3 or 10 mg/kg, three doses) has no longlasting effects on brain tissue monoamines (Baumann et al, 2012), but administration of higher doses of mephedrone to group-housed rats (10 or 25 mg/kg, s.c., four doses) causes selective depletion of brain serotonin (Hadlock et al, 2011). It is noteworthy that MDPV is the chief substance detected in blood and urine from patients hospitalized for bath salts overdose in the US (Spiller et al, 2011).…”
mentioning
confidence: 99%
“…The fact that synthetic cathinones enhance dopamine transmission predicts high abuse liability. Hadlock et al (2011) reported that i.v. mephedrone (0.24 mg/infusion) is readily self-administered by rats, but reinforcing effects of other synthetic cathinones are largely unexplored.…”
mentioning
confidence: 99%